2022
DOI: 10.1021/acsnano.1c08664
|View full text |Cite
|
Sign up to set email alerts
|

Multienzyme-like Reactivity Cooperatively Impairs Glutathione Peroxidase 4 and Ferroptosis Suppressor Protein 1 Pathways in Triple-Negative Breast Cancer for Sensitized Ferroptosis Therapy

Abstract: Ferroptosis is a recently discovered route of regulated cell death that offers the opportunities for the treatment of chemotherapy-resistant tumor indications, but its efficacy can be affected by the glutathione peroxidase 4 (GPX4) and ferroptosis suppressor protein 1 (FSP1) antioxidant mechanisms, posing significant challenges for its clinical translation. In this study, we report a Cu-tetra­(4-carboxyphenyl)­porphyrin chloride­(Fe­(III)) (Cu-TCPP­(Fe)) metal organic framework (MOF)-based nanosystem for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(94 citation statements)
references
References 57 publications
2
92
0
Order By: Relevance
“…Multiple lines of evidence have suggested ferroptosis’ pivotal role in tumor suppressor pathways, including p53 activation, highlighting its relevance in the field of antineoplastic therapies [ 5 , 6 ]. Indeed, several studies have demonstrated the high potential of ferroptosis as a novel therapeutic strategy for the treatment of different cancers, including hepatic, lung and breast cancer [ 7 , 8 , 9 , 10 , 11 , 12 ]. Recent studies have confirmed that female breast cancer (BC) has overtaken lung cancer as the most commonly diagnosed cancer, with an estimated 2.3 million new cases (11.7%), closely followed by lung (11.4%), colorectal (10.0%), prostate (7.3%) and stomach (5.6%) cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple lines of evidence have suggested ferroptosis’ pivotal role in tumor suppressor pathways, including p53 activation, highlighting its relevance in the field of antineoplastic therapies [ 5 , 6 ]. Indeed, several studies have demonstrated the high potential of ferroptosis as a novel therapeutic strategy for the treatment of different cancers, including hepatic, lung and breast cancer [ 7 , 8 , 9 , 10 , 11 , 12 ]. Recent studies have confirmed that female breast cancer (BC) has overtaken lung cancer as the most commonly diagnosed cancer, with an estimated 2.3 million new cases (11.7%), closely followed by lung (11.4%), colorectal (10.0%), prostate (7.3%) and stomach (5.6%) cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Coenzyme Q10 (CoQ10), an important electron carrier in the mitochondrial electronic respiratory chain, is an effective RONS scavenger [ 239 ]. However, CoQ10 is hydrophobic and cannot be directly used in AKI treatment.…”
Section: Nanocarriers For Antioxidants and Anti-inflammatory Drugsmentioning
confidence: 99%
“…Mimetic drugs composed of small-molecule inducers of ferroptosis, erastin, and RSL3 with BH3 were effective in synergistically killing U251 cells and inhibiting malignant progression of glioblastoma ( 111 ). Nanocatalytic activity leads to simultaneous inhibition of GPX4/GSH and FSP1/coq10h2 pathways and synergizes with the GPX4 inactivation function of RSL3 to cause significant ferroptosis damage and thus inhibit malignant progression of triple-negative breast cancer ( 112 ). Depletion of PSTK leads to inactivation of GSH peroxide 4 (GPX4) and inhibition of selenocysteine and cysteine synthesis.…”
Section: Role Of Ferroptosis Necroptosis and Pyroptosis In Tumorsmentioning
confidence: 99%